2011
DOI: 10.3389/fmicb.2010.00148
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Microbial Fatty Acids in the Human Metabolome are Disease-Specific

Abstract: The human gastrointestinal tract is inhabited by a diverse and dense symbiotic microbiota, the composition of which is the result of host–microbe co-evolution and co-adaptation. This tight integration creates intense cross-talk and signaling between the host and microbiota at the cellular and metabolic levels. In many genetic or infectious diseases the balance between host and microbiota may be compromised resulting in erroneous communication. Consequently, the composition of the human metabolome, which includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 50 publications
(58 reference statements)
3
24
0
2
Order By: Relevance
“…Correspondingly, the profile of microbial LCFAs circulating in the blood is also specific for the diseased and healthy states (Ktsoyan et al, 2010). In this work, we addressed the question whether the colchicine therapy that is used to suppress the clinical manifestations of FMF and to extend the remission periods could also have an effect on the level and profile of microbial LCFAs in systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Correspondingly, the profile of microbial LCFAs circulating in the blood is also specific for the diseased and healthy states (Ktsoyan et al, 2010). In this work, we addressed the question whether the colchicine therapy that is used to suppress the clinical manifestations of FMF and to extend the remission periods could also have an effect on the level and profile of microbial LCFAs in systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that this autoinflammatory condition results in cardinal restructuring of gut microbiota (Khachatryan et al, 2008), accompanied by changes in microbial products circulating in the systemic metabolome (Ktsoyan et al, 2010). We also demonstrated the increased systemic reactivity against the commensal gut microbiota in FMF, thus suggesting a possible mechanism for restructuring the gut microbiota composition in an autoinflammatory condition (Manukyan et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other odd-carbon fatty acids, such as hentriancontanoic acid (C 31 H 62 O 2 ), nonacosanoic acid (C 29 H 58 O 2 ), heptacosanoic acid (C 27 H 54 O), and the methyl-branched iso-heptadecanoic acid (iso-C 17 H 34 O 2 ), exhibited similar accumulation patterns, the latter of which increased by almost 21-fold. Since these are higher order and have odd numbers of carbon atoms, they are likely of microbial origin [30]. The accumulation of these long-chain, saturated fatty acids, and unique branched fatty acids, indicates cell membrane restructuring to better tolerate increased concentrations of lignocellulose-derived inhibitors that affect membrane fluidity [3133].…”
Section: Resultsmentioning
confidence: 99%
“…Both approaches were implemented; however, it is unlikely that they can be considered universal. Minor acids (see [47,52]) are most often considered to be biomarkers; their identification against the background of intense analytical signals of nonspecific compounds in the presence of a great number of isomers (formally appearing in the shift of double bonds in the aliphatic chain and its branching) can, in our opinion, be unre liable. The biomarker approach is, probably, most promising for the recognition of certain genus and species of bacteria [48,49].…”
Section: Identification Of Microorganismsmentioning
confidence: 99%